Monitoring Leaf Nitrogen Accumulation With Optimized Spectral Index in Winter Wheat Under Different Irrigation Regimes - Sun, Hui; Feng, Meichen; Yang, Wude; Bi, Rutian; Sun, Jingjing; Zhao, Chunqi; Xiao, Lujie; Wang, Chao; Kubar, Muhammad Saleem (Frontiers in Plant Science, 2022)
Rapid and non-destructive estimation of leaf nitrogen accumulation (LNA) is essential to field nitrogen management. Currently, many vegetation indices have been used for indicating nitrogen status. Few studies systematically analyzed the performance of vegetation indices of winter wheat in estimating LNA under different irrigation regimes. This study aimed to develop a new spectral index for LNA estimation. In this study, two years of field experiments with different irrigation regimes were conducted from 2015 to 2017. The original reflectance (OR) and three transformed spectra (e.g. the first derivative reflectance (FDR), logarithm of the reciprocal of the spectra (Log(1/R)) and continuum removal (CR)) were used to calculate two-band and three-band spectral indices. Correlation analyses and univariate linear and non-linear regression between transformed-based spectral indices and LNA were performed. The performance of the optimal spectral index was evaluated with classical vegetation index. The results showed that FDR was the most stable transformation method which can effectively enhance the relationships to LNA and improve prediction performance. With a linear relationship with LNA, FDR-based three-band spectral index 1 (FDR-TBI1) (451, 706, 688) generated the best performance with coefficient of determination (R2) of 0.73 and 0.79, the root mean square error (RMSE) of 1.267 g/m2 and 1.266 g/m2 and the ratio of performance to interquartile distance (RPIQ) of 2.84 and 2.71 in calibration and validation datasets, respectively. The optimized spectral index (FDR-TBI1 (451, 706, 688)) are more effective and might be recommended as an indicator for estimating winter wheat LNA under different irrigation regimes.